Effectiveness of fluticasone furoate plus vilanterol on asthma control in clinical practice: an open-label, parallel group, randomised controlled trial. Issue 10109 (18th November 2017) - Woodcock, Ashley; Vestbo, Jørgen; Bakerly, Nawar Diar; New, John; Gibson, J Martin; McCorkindale, Sheila; Jones, Rupert; Collier, Susan; Lay-Flurrie, James; Frith, Lucy; Jacques, Loretta; Fletcher, Joanne L; et al.
Summary: Background: Evidence for management of asthma comes from closely monitored efficacy trials done in highly selected patient groups. There is a need for randomised trials that are closer to usual clinical practice. Methods: We did an open-label, randomised, controlled, two-arm effectiveness trial at 74 general practice clinics in Salford and South Manchester, UK. Patients aged 18 years or older with a general practitioner's diagnosis of symptomatic asthma and on maintenance inhaler therapy were randomly assigned to initiate treatment with a once-daily inhaled combination of either 100 μg or 200 μg fluticasone furoate with 25 μg vilanterol or optimised usual care and followed up for 12 months. The primary endpoint was the percentage of patients who achieved an asthma control test (ACT) score of 20 or greater or an increase in ACT score from baseline of 3 or greater at 24 weeks (termed responders), in patients with a baseline ACT score less than 20 (the primary effectiveness analysis population). All effectiveness analyses were done according to the intention-to-treat principle. This study is registered withClinicalTrials.gov, numberNCT01706198 . Findings: Between Nov 12, 2012, and Dec 16, 2016, 4725 patients were enrolled and 4233 randomly assigned to initiate treatment with fluticasone furoate and vilanterol (n=2114) or usual care (n=2119). 1207 patients (605 assigned to usual care, 602 to fluticasone furoate and vilanterol) had a baseline ACT score greater than or equal to 20 and were thus excluded from the primary effectiveness analysis population. At week 24, the odds of being a responder were higher for patients who initiated treatment with fluticasone furoate and vilanterol than for those on usual care (977 [71%] of 1373 in the fluticasone furoate and vilanterol group vs 784 [56%] of 1399 in the usual care group; odds ratio [OR] 2·00 [95% CI 1·70–2·34], p<0·0001). At week 24, the adjusted mean ACT score increased by 4·4 points from baseline in patients initiated with fluticasone furoate and vilanterol, compared with 2·8 points in the usual care group (difference 1·6 [95% CI 1·3–2·0], p<0·0001). This result was consistent for the duration of the study. Pneumonia was uncommon, with no differences between groups; there was no difference in other serious adverse events between the groups. Interpretation: In patients with a general practitioner's diagnosis of symptomatic asthma and on maintenance inhaler therapy, initiation of a once-daily treatment regimen of combined fluticasone furoate and vilanterol improved asthma control without increasing the risk of serious adverse events when compared with optimised usual care. Funding: GlaxoSmithKline.